2-ABSORBING INTUITIONISTIC FUZZY IDEALS OF COMMUTATIVE SEMIRINGS - Ozkan, Erdogan Mehmet; Onar, Serkan; Ozkan, Ayten; Ayan, Rabia (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2023)
The purpose of this study is to define the 2-absorbing intuitionistic fuzzy ideals and 2-absorbing intuitionistic fuzzy primary ideals of commutative semirings, as well as to describe their characteristics. Furthermore, we define the cartesian product of the 2 -absorbing intuitionistic fuzzy primary ideals of commutative semirings.
Keywords: 2-absorbing ideal; 2-absorbing primary ideal; 2-absorbing intuitionistic fuzzy ideal; PRIME IDEALS; Science & Technology - Other Topics